The Variations in Verb-Preposition Combinations in the GloWbE Corpus and Its Usage in Informal Englishes - Hossain, Kazi Amzad (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
This paper is based on the Corpus of Global Web-based English (GloWbE) which was compiled by Mark Davies in 2013. The GloWbE corpus consists of web data from 20 different English speaking countries. This research is constructed on the GloWbE corpus to investigate the variations in certain verb-preposition combinations in informal Englishes. As the corpus is divided into two sections, such as – general and blog, this study is based on the blog section to compare web data from two inner circle countries such as The USA and Great Britain and two outer circle countries such as – India and Bangladesh. The reason for selecting the blog is that, in the GloWbE corpus, blog section consists of informal data, whereas general section consists of formal data. It is to be noted that the inner circle countries use English as their native tongue, whereas the outer circle countries use English as their second or foreign language. This paper argues that, the verb-preposition combinations or prepositional verbs vary in their frequency and meaning in the aforementioned countries and this paper investigates the following five prepositional verbs from The Cambridge Grammar of the English Language proposed by Huddleston and Pullum in 2002– come up with, look out for, put up with, stand up to, and get along with in the GloWbE corpus to prove that the frequency and meaning of these phrases varies from country to country based on social, cultural and political contexts as seen in the results. The investigation specifically shows the trends of the above five prepositional verbs in the four countries.